Challenges and solutions for multimodal analysis: Technology, theory and practice - O'Halloran, Kay; Podlasov, A.; Chua, A.; Tisse, C.; Lim, F.; Smith, B. (Equinox, 2014)
Multimodal analysis, also called multimodal discourse analysis (MDA) and more generally 'multimodality', is a rapidly expanding interdisciplinary field in linguistics and language-related fields of study, including education. Multimodal analysis is concerned with theorizing and analysing the multiple resources (eg. language, image, audio resources, embodied action and three-dimensional objects) which combine to create meaning in different contexts (eg .print media, film, digital media, and day-to-day events). Inspired by Kress and van Leeuwen, and O'Toole foundational works in the mid 1990s, muliltmodal research has largely derived from Michael Halliday's social semiotic theory which provides a comprehensive theoretical platform for the study of semiotic resources and their integration in media and events.